Penerapan Range of Motion (ROM) Pasif pada Asuhan Keperawatan Pasien Stroke dengan Gangguan Mobilitas Fisik di Ruang Stroke Unit RSD Gunung Jati Kota Cirebon - Rama Sukma Diraja; Nonok Karlina (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Stroke is one of the degenerative diseases that is the main cause of death and disability in Indonesia. Based on WHO data in 2022, there are more than 12 million new cases of Stroke every year worldwide, while the prevalence of Stroke in Indonesia reaches 12.1 per 1,000 population (Riskesdas 2018). One of the nursing problems that often arise in Stroke patients is impaired physical mobility due to muscle weakness and immobilization. Range of Motion (ROM) exercises are a rehabilitation intervention that has been shown to be effective in increasing muscle strength and preventing joint stiffness. This study aims to describe the implementation of ROM exercises in Stroke patients with physical mobility disorders at Gunung Jati Hospital, Cirebon City in 2026. The research design was in the form of a qualitative descriptive case study with the subject Mr. A, a 48-year-old male with a diagnosis of non-hemorrhagic Stroke. Passive and active ROM interventions were carried out for three days in a structured manner. The evaluation showed an improvement in the patient's movement ability and muscle strength, so that nursing problems were partially resolved. The results of the study confirm that regular and repeated ROM exercises are effective in improving physical mobility and muscle strength in non-hemorrhagic Stroke patients. Education to patients and families also plays an important role in supporting the rehabilitation and recovery process.